Parental support and pressure on athletes of high school students in Marang district / Mohamad Afiq Alias - Alias, Mohamad Afiq (Faculty of Sport Science and Recreation, 2018)
The purpose of this study was to evaluate the level of parental support and pressure on athletes among high school students in the Marang district. A total of eighty athletes (N=80) were involved via purposive sampling in this study. The study was descriptive and used demographic questionnaire and (The Athlete Questionnaire support and pressure) as the intruments of data collection. Based on the discriptive statistics, the total parental support level is high which is 63.24 (SD=9.13) The total parental pressure level is also high which is 33.35 (SD=6.70). The results also show that there is a significant relationship (p = 0.000, r = -0.778) between parental support and parental pressure among high school students. In addition, the results for the independent T-Test, show that there is no significant different relationship between team and individual sports. There is no significant difference between the level of parental support and type of sport, which is p 0.34, p<O.05 for type of parental support and 0.96,p<O.05 for parental pressure. The researcher evaluated the level of parental support and pressure among high school students in the Marang district. Furthermore, the researcher also evaluated the correlation between the level of parental support and pressure among school student in the Marang district.